Supply chain risk management and the efficiency of engineer-to-order projects - Liao, Chuilian (2020)
Purpose: The purpose of this research is to explore how supply chain risk management influences the efficiency of ETO projects, as well as provide some theoretical and managerial implications. Design/methodology/approach: Based on the literature review involving supply chain risk management and ETO projects, two case studies of ETO companies in the construction industry were conducted to understand the relationship between supply chain risk management in ETO projects and their efficiency. A thorough comparison and analysis were conducted to respond to the research questions. Findings: The findings show that positive preventive risk management and positive corrective risk management can improve project efficiency and positive preventive risk management and positive corrective risk management can benefit each other. Research limitations: It is based on two cases, which means it needs to be tested if it can be generalized to a broader level. Moreover, all the interviews were conducted by the author, causing certain limitation. Furthermore, the two companies were the Type II ETO companies. It would be interesting if researches could study other types of ETO companies to further validate the conclusions. Originality/value: This is the first study which explores how preventive risk management (PRM) and corrective risk management (CRM) influence project efficiency in terms of project functionality, project cost, construction period and project construction respectively, and how PRM and CRM influence each other. It demonstrates that PRM and CRM are quite important to project efficiency and managers can learn from corrective risk management and make better decisions in subsequent risk prevention.